2011
DOI: 10.1128/jb.05061-11
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Cloned RhsA Sequences Perturbs the Cellular Translational Machinery in Escherichia coli

Abstract: RhsA is a member of the multigene Rhs family and consists of a complex genetic sequence. This sequence consists of several distinct components, including a GC-rich core (core open reading frame [ORF]), an AT-rich extension (ext-a1) of the core ORF and an AT-rich region following the core extension (dsORF-a1). The functions of RhsA and the different distinct components, which can include open reading frames, are not well understood. Here, we study the effect of overexpression of the ext-a1 sequence and the ext-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Early studies found that the E. coli rhsA core extension inhibits recovery from stationary phase (17), and recent work suggests that this toxin inhibits protein synthesis (18). Additionally, a plasmid-encoded Rhs protein has been implicated in bacteriocin production in Pseudomonas savastanoi (19).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies found that the E. coli rhsA core extension inhibits recovery from stationary phase (17), and recent work suggests that this toxin inhibits protein synthesis (18). Additionally, a plasmid-encoded Rhs protein has been implicated in bacteriocin production in Pseudomonas savastanoi (19).…”
Section: Discussionmentioning
confidence: 99%
“…There is also an rhsA gene and 3 rhs-like elements. RhsA, a nuclease, has been shown to affect the expression of genes involved in transcription, RNA processing, nucleotide biosynthesis and metabolism, and amino acid biosynthesis in E. coli (37). rhsA is also embedded in the T6SS gene cluster in Dickeya dadantii and is likely to be exported through the T6SS (38).…”
Section: Discussionmentioning
confidence: 99%
“…This effect could be impeded by the coexpression of a downstream gene (Vlazny & Hill, 1995), apparently functioning as an antitoxin module. Subsequently, Aggarwal and Lee demonstrated that the RhsA function interferes with transcription and translation, though the exact mechanism of its action remains unknown (Aggarwal & Lee, 2011). In P. savastanoi pv.…”
Section: Inhibitory Activities Of Rhs Systemsmentioning
confidence: 99%